Genomic signatures of hybridization between Ixodes ricinus and Ixodes persulcatus in natural populations - Alale, Theophilus Yaw (Wiley, 2025)
Identifying hybridization between common pathogen vectors is essential due to the major public health implications through risks associated with hybrid's enhanced pathogen transmission potential. The hard-ticks Ixodes ricinus and Ixodes persulcatus are the two most common vectors of tick-borne pathogens that affect human and animal health in Europe. Ixodes ricinus is a known native species in Finland with a well-known distribution, whereas I. persulcatus has expanded in range and abundance over the past 60 years, and currently it appears the most common tick species in certain areas in Finland. Here we used double-digest restriction site-associated DNA (ddRAD) sequencing on 186 ticks (morphologically identified as 92 I. ricinus, and 94 I. persulcatus) collected across Finland to investigate whether RAD generated single nucleotide polymorphisms (SNPs) can discriminate tick species and identify potential hybridization events. Two different clustering methods were used to assign specific species based on how they clustered and identified hybrids among them. We were able to discriminate between the two tick species and identified 11 putative hybrids with admixed genomic proportions ranging from approximately 24 to 76 percent. Four of these hybrids were morphologically identified as I. ricinus while the remaining seven were identified as I. persulcatus. Our results thus indicate that RAD SNPs are robust in identifying both species of the ticks as well as putative hybrids. These results further suggest ongoing hybridization between I. ricinus and I. persulcatus in their natural populations in Finland. The unique ability of RAD markers to discriminate between tick species and hybrids adds a useful aspect to tick evolutionary studies. Our findings align with previous studies and suggest a shared evolutionary history between the species, with instances of individuals possessing a considerable proportion of the other species' genome. This study is a significant step in understanding the formation of hybridization zones due to range expansion potentially associated with climate change.